23.4% Hypertonic Saline and Intracranial Pressure in Severe Traumatic Brain Injury Among Children: A 10-Year Retrospective Analysis. Issue 5 (May 2019) - Wu, Andrew G.; Samadani, Uzma; Slusher, Tina M.; Zhang, Lei; Kiragu, Andrew W.
Abstract : Objective: To explore the effect of 23.4% hypertonic saline for management of elevated intracranial pressure in children admitted to our institution for severe traumatic brain injury. Design: Single-center, retrospective medical chart analysis. Setting: A PICU at a level 1 pediatric trauma center in the United States. Patients: Children admitted for severe traumatic brain injury from 2006 to 2016 who received 23.4% hypertonic saline and whose intracranial pressures were measured within 5 hours of receiving 23.4% hypertonic saline. Interventions: None. Measurements and Main Results: Over the 10-year period, 1, 587 children were admitted for traumatic brain injury, 155 of whom were deemed severe per this study's criteria. Forty of these children received at least one dose of hypertonic saline, but 14 were excluded for insufficient intracranial pressure data. Among the remaining 26 children, one hundred one 23.4% hypertonic saline boluses were used in the analysis. Use of 23.4% hypertonic saline was associated with a decrease in intracranial pressure of approximately 7 mm Hg at both within 1 hour after the bolus ( p < 0.01) and 4 hours after the bolus ( p < 0.01) when compared with the intracranial pressure measured within 1 hour before the hypertonic saline bolus. These effects remained significant after adjusting for Functional Status Scale score and CT Marshall scores. There was no statistically significant association between adjunctive therapies, such as antiepileptics and analgesics, and changes in intracranial pressure. There was no laboratory evidence of hyperkalemia or renal injury after use of 23.4% hypertonic saline. Across all hospitalizations, 65% of the study population demonstrated an abnormally elevated creatinine at least once, but only three episodes of acute kidney injury occurred in total, all before hypertonic saline administration. Eight of the 26 children in this analysis died during their hospitalization. The Functional Status Scale scores ranged from 6 to 26 with a mean of 12.2 and SD of 5.7. Conclusions: Use of 23.4% hypertonic saline with children admitted for severe traumatic brain injury is associated with a statistically significant decrease in intracranial pressure within 1 hour of use. Abstract : Supplemental Digital Content is available in the text.